Induced Thermotolerance and Expression of Three Key Hsp Genes (Hsp70, Hsp21, and sHsp21) and Their Roles in the High Temperature Tolerance of Agasicles hygrophila - Jin, Jisu; Zhao, Meiting; Wang, Yao; Zhou, Zhongshi; Wan, FangHao; Guo, Jianying (Frontiers in Physiology, 2020)
Thermal adaptation plays a fundamental role in the expansion and distribution of insects, and heat shock proteins (Hsps) play important roles in the temperature adaptation of various organisms. To determine the roles of Hsp genes (Hsp70, Hsp21, and sHsp21) on the high temperature tolerance of Agasicles hygrophila, we obtained complete cDNA (complementary DNA) sequences for Hsp70, Hsp21, and sHsp21 by rapid amplification of cDNA ends (RACE), analyzed their expression profiles under different high temperature treatments by quantitative reverse transcription polymerase chain reaction (RT-qPCR), and performed functional verification by RNA interference (RNAi). The open reading frames (ORFs) of Hsp70, Hsp21, and sHsp21 were 1940, 664, and 567 bp, encoding 650, 180, and 188 amino acids, respectively. Their molecular weights (MWs) were 71.757, 20.879, and 21.510 kDa, and the isoelectric points were 5.63, 6.45, and 6.24, respectively. Phylogenetic tree analysis showed that the Hsp70, Hsp21, and sHsp21 genes of A. hygrophila were relatively conserved in evolution. The Hsp70 and Hsp21genes in A. hygrophila were homologous to those in Leptinotarsa decemlineata (87% and 79% similarity, respectively), and the sHsp21 gene in A. hygrophila was homologous to that in Lissorhoptrus oryzophilus (74% similarity). The amino acid polypeptide chain had highly conserved sequences of DLGGGTFD, VLVGGSTR, and GPTIEEVD. The sequence of EEVD was the characteristic motif of cytoplasmic Hsp70, and the highly conserved sequences of MALFR and MSLLP were characteristic sequences of Hsp2 and sHsp21, respectively. Real-time fluorescence quantitative PCR showed that the three Hsps could be induced by 4-h treatment at high temperatures. Significant upregulation of these Hsps was observed when the temperature was further increased. The RNAi results showed that the injection of the three Hsps’ dsRNA could suppress the expression at the gene level signiﬁcantly. Compared with the control group, high temperature heat shock reduced the fecundity of A. hygrophila significantly, and the fecundity decreased with the increase in temperature. Our results suggest that Hsp70, Hsp21, and sHsp21 might play key roles in high temperature adaptation of A. hygrophila and help improve our understanding of their mechanism of thermotolerance.